2021
DOI: 10.1007/jhep07(2021)146
|View full text |Cite
|
Sign up to set email alerts
|

Boosting background suppression in the NEXT experiment through Richardson-Lucy deconvolution

Abstract: Next-generation neutrinoless double beta decay experiments aim for half-life sensitivities of ∼ 1027 yr, requiring suppressing backgrounds to < 1 count/tonne/yr. For this, any extra background rejection handle, beyond excellent energy resolution and the use of extremely radiopure materials, is of utmost importance. The NEXT experiment exploits differences in the spatial ionization patterns of double beta decay and single-electron events to discriminate signal from background. While the former display two Br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…The ratio of the signal efficiency over the square root of the background acceptance ranges from ≈2.3 to ≈3.1 for events between 1 and 3 MeV energy, consistent with Ref. [15]. According to this selection, the top and bottom panels of Fig.…”
Section: Event Reconstruction and Selectionsupporting
confidence: 85%
See 1 more Smart Citation
“…The ratio of the signal efficiency over the square root of the background acceptance ranges from ≈2.3 to ≈3.1 for events between 1 and 3 MeV energy, consistent with Ref. [15]. According to this selection, the top and bottom panels of Fig.…”
Section: Event Reconstruction and Selectionsupporting
confidence: 85%
“…The deconvolved 3D hits are then grouped into volume elements of (5 mm) 3 , which are used to build tracks following the connectivity criteria established by a breadth-first search algorithm [16]. The energies of the endpoints of each track, hereafter "blobs," are defined by integrating the energy of the hits contained within spheres of 18 mm in radius centered in the identified extremes [15]. Figure 3 shows examples of two observed tracks of 1.7 MeV.…”
Section: Event Reconstruction and Selectionmentioning
confidence: 99%
“…Tracking information is obtained from a SiPM array at the anode, while PMTs at the cathode provide optimal energy resolution. NEXT-White (Monrabal et al, 2018), a proof-of-principle detector with 5 kg of Xe at 10 bar, demonstrated an energy resolution of σ = 10 keV at Q ββ (Renner et al, 2019), and tracking performance capable of discriminating sin-gle and double electron track events, retaining 57% of signal events while rejecting background by a factor of 27 (Simón et al, 2020). A second stage, NEXT-100 (Alvarez et al, 2012;Martín-Albo et al, 2016), with a pressure of 15 bar and containing 87 kg of 136 Xe, is currently under construction.…”
Section: Xenon Time Projection Chambersmentioning
confidence: 99%
“…On the other hand, for high-energy events, the threshold is increased to 10 photoelectrons per 1 µs time slice. This value was identified as the optimal threshold for track reconstruction [ 23 ]. Still, given the non-reversibility nature of lossy compression, a heavily conservative ZS configuration was chosen for standard data-taking.…”
Section: Next Experiments Data Compression Studymentioning
confidence: 99%